EFECTO INHIBITORIO DEL TRATAMIENTO MAGNÉTICO DE FRECUENCIA EXTREMADAMENTE BAJA SOBRE LA MICROBIÓTA TÍPICA DE MELAZA - Anaya Villalpanda, Matilde; Guzmán Armenteros, Tania; Vivar Pérez, Alexander; Cobo Almaguer, Hilda; Acea Fiallo, Carlos (Tsafiqui, 2013)
The following research was aimed to evaluat of the inhibitory effect of an oscillating magnetic field (OMF) of low frequency (60 Hz) and density (6.5 mT) on typical microbiota of molasses to different concentrations. The experimental factors were OMF treatment time (0, 30 y 60 min) and molasses concentration (12, 18 y 24 °Bx). Response variable to evaluate was the count of total aerobic mesophilic (total count) and of fungi and yeast, by culture in dishes and as in log cfu/mL. In general, microorganism decrease did not achieve the logarithmic unit and in a decrease of 0.5% compared to control was obtained. Higher incidence of microbiota in the order: bacteria, yeasts and filamentous fungi were observed, they were most resistance to magnetic treatment. The most effective treatment time in all groups of microorganisms was 60 min and fundamentally on dilution at 12°Bx. Was concluded that an OMF low value density applied under identical conditions to a study sample may have inhibitory effect on undesirable microorganisms that form the typical microbiota of a given substrate. It was demonstrated that there is not necessarily a direct relationship between the applied magnetic field density and reduced microbial content.